Christian Community and the Promotion of Healing: Theological Reflection in a Therapeutic Context - Sheehan, Mary Ellen (Toronto journal of theology, 1985)
Emily Dickinson, a well known nineteenth century New England poet, spent much of her creative gift in describing starkly the raw experience of psychic suffering. She often dwelt on the solitary and separating character of suffering, even to the point of insinuating frequently in her poetry that the afflicted one is beyond any form of human consolation.